The scientific production of health professionals about female homosexuality and Papanicolau: bibliometric study (Research, Society and Development, 2022)
This study aims to bibliotechnically analyze scientific production through articles published in journals on female homosexuality and the Pap smear in the period from 2016 to 2020. Method: This is a bibliometric, descriptive study with a quantitative approach. Results: A total of 1,055 publications related to the topic between the years 2010 to 2020 were evidenced, distributed in 619 journals and with publications in 68 countries. Discussion: there was a large margin that presents itself in the rise of publications related to female homosexuality and the Pap smear. Conclusion: In view of the results presented in this study, it was evident that in the period proposed for the research, the years 2010 – 2020, there was a large margin that presents an increasing number of publications on the subject.